If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 3x = 4x + -8 Reorder the terms: -4 + 3x = -8 + 4x Solving -4 + 3x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 3x + -4x = -8 + 4x + -4x Combine like terms: 3x + -4x = -1x -4 + -1x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + -1x = -8 + 0 -4 + -1x = -8 Add '4' to each side of the equation. -4 + 4 + -1x = -8 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -8 + 4 -1x = -8 + 4 Combine like terms: -8 + 4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| 3a(6a-5)+4=10 | | 6=w+37 | | 3x-4/2=4 | | 4x-1=-2x+12 | | m+1/2=5 | | 3ax-x= | | 2/3x+5/5x | | 3x+5=-10+x | | 10.35(3)(15)=a | | x^2+2/3x-26/9 | | 6/8x=72 | | 33(x+2/5)=x-1/3 | | 10.35(3)(15)=465.75 | | x^2+y^2+10x+12y+61=0 | | -4x+6=3x+-8 | | 1000/9.81 | | 52-3x=24x+16 | | 1+x^4-2x^2+1.96x^2=1.0096x^4 | | -6x+7=10-5x | | 60+.6x=.8x | | (w+8)(w-3)=0 | | 60+.6=.2 | | 5x+10=64-4x | | 5y^2+9=3y | | y^2=6y+7 | | 6x+13=35-3x | | (3d+2)(7-1)=0 | | -4x-10=46+5x | | (1/3x)=9 | | 4x+1=60 | | 5x-16=4x+5 | | x-10=-21+2x |